Valuation of Water Service Fee for Tidal Lowland Agriculture in South Sumatra - Yazid, Muhammad (2010)
Water management is a key factor in tidal lowland agriculture with three-fold objectives of improving water allocation, recovering costs, and achieving efficient water distribution. In order to achieve these objectives, water management infrastructures must be properly operated and maintained. Therefore, besides the established guidelines for operation and maintenance (OM), the availability of fund is required to carry out proper OM and ensure the achievement of water management objectives (WMO). OM is financed by both government and water users through water service fee (WSF). However, neither government budget nor WSF is sufficient to finance OM at its respective level of water management. WSF is insufficient to finance OM at tertiary level since there is no reliable measures of WSF for which farmers are responsible to contribute. The valuation of WSF for tidal lowland agriculture is aimed at: (i) the estimation of WSF; (ii) the estimation of willingness to pay (WTP) for WSF and its affecting factors; and (iii) the evaluation of the achievement of WMO. The results of this study are expected to contribute to the growth of knowledge in water resource management and to the formulation of policy in accordance to the achievement of sustainable water management in tidal lowland agriculture. This study employs the following methods: (i) participatory field observation and focus group discussion for WSF estimation based on the costs of water delivery; (ii) production function estimation for WSF estimation based on the value of water service in crop production; (iii) contingent valuation method (CVM) for the estimation of WTP for WSF; (iv) hedonic pricing (HP) for the estimation of WTP for WSF to complement CVM. Data are collected through field survey at the tidal lowland area of Telang I, South Sumatra, Indonesia. Respondents are selected using stratified random sampling. The results of this study include three WSF estimates based on the cost of water distribution. WSF1 is amounted Rp 315,000 per hectare to indicate the supply cost, WSF2 is amounted Rp 346,500 per hectare to account for economic cost, and WSF3 is amounted Rp 391,500 per hectare to reflect the full cost. In comparison, the benefit of water service in crop production is Rp 455,700 per hectare, which is higher than any types of cost of water distribution. Water service is proved to be a significant determinant of crop production.